Immunoprofiles of 11 Biomarkers Using Tissue Microarrays Identify Prognostic Subgroups in Colorectal Cancer - Knösel, Thomas (Neoplasia Press Inc., 2005)
BACKGROUND AND AIMS: Genomewide expression profiling has identified a number of genes expressed at higher levels in colorectal cancer (CRC) than in normal tissues. Our objectives in this study were: 1) to test whether genes were also distinct on the protein level; 2) to evaluate these biomarkers in a series of well-characterized CRCs; and 3) to apply hierarchical cluster analysis to the immunohistochemical data. METHODS: Tissue microarrays (TMAs) comprising 351 CRC specimens from 270 patients were constructed to evaluate the genes Adam10, CyclinD1, AnnexinII, NFKB, Casein-kinase-2-beta (CK2B), YB-1, P32, Rad51, c-fos, IGFBP4, and Connexin26 (Cx26). In total, 3,797 samples were analyzed. RESULTS: Unsupervised hierarchical clustering discovered subgroups of CRC that differed by tumor stage and survival. Kaplan-Meier analysis showed that reduced Cx26 expression was significantly associated with shorter patient survival and higher tumor grade (G(1)/G(2) vs G(3), P = .02), and Adam10 expression with a higher tumor stage (pT(1/2) vs pT3/4, P = .04). CONCLUSIONS: Our study highlights the potential of TMAs for a higher-dimensional analysis by evaluating serial sections of the same tissue core (three-dimensional TMA analysis). In addition, it endorses the use of immunohistochemistry supplemented by hierarchical clustering for the identification of tumor subgroups with diagnostic and prognostic signatures.